2021
DOI: 10.1021/acsnano.0c08822
|View full text |Cite
|
Sign up to set email alerts
|

Label-Free Ultrasensitive Detection of Abnormal Chiral Metabolites in Diabetes

Abstract: Homochirality is necessary for normal biochemical processes in humans. Abnormal amounts of chiral molecules in biofluids have been found in patients with diabetes. However, the detailed analysis of diabetes-related abnormal chirality in biofluids and its potential use for clinical applications have been hindered by the difficulty in detecting and monitoring the chiral changes in biofluids, due to their low molar mass and trace concentrations. Herein, we demonstrate the label-free detection of chiral molecules … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 53 publications
0
30
0
Order By: Relevance
“…[5][6][7][8][9][10][11][12] However, natural chiral molecules have an extremely weak CD signal since their sizes do not match the wavelength of the incident light, in the range of only a few tens of millidegrees in the ultraviolet region. [13] Inspired by the chiral objects in the physical world, artificial chiral nanostructures made by advanced micro/nanofabrication techniques have attracted tremendous attention for their conspicuous chiroptical effects, [14][15][16][17][18][19] leading to versatile applications such as biosensors, [20][21][22][23][24][25][26][27] miniaturized polarizers, [28][29][30][31][32] metamirrors, [33][34][35] and detectors. [36][37][38] Several schemes have been developed to fabricate chiral metamaterials.…”
Section: Doi: 101002/adma202203956mentioning
confidence: 99%
“…[5][6][7][8][9][10][11][12] However, natural chiral molecules have an extremely weak CD signal since their sizes do not match the wavelength of the incident light, in the range of only a few tens of millidegrees in the ultraviolet region. [13] Inspired by the chiral objects in the physical world, artificial chiral nanostructures made by advanced micro/nanofabrication techniques have attracted tremendous attention for their conspicuous chiroptical effects, [14][15][16][17][18][19] leading to versatile applications such as biosensors, [20][21][22][23][24][25][26][27] miniaturized polarizers, [28][29][30][31][32] metamirrors, [33][34][35] and detectors. [36][37][38] Several schemes have been developed to fabricate chiral metamaterials.…”
Section: Doi: 101002/adma202203956mentioning
confidence: 99%
“…Liu et al implemented BPL on plasmonic chiral metamaterials for the diagnosis of diabetes through the ultrasensitive label-free detection of abnormal chiral metabolites in urine. [113] First, the urine samples were purified through centrifugation to remove all macromolecules and cells (Figure 5A). A plasmonic moire chiral metamaterial (MCM) [114][115][116]51] was used to gener-ate optothermal microbubbles and enable the high-sensitive chiral measurement of immobilized molecules with plasmonenhanced superchiral fields.…”
Section: Bpl For Clinical Detection Of Diabetesmentioning
confidence: 99%
“…Many chiral molecules in human body exhibit the phenomenon of homochirality, where one of the enantiomers is dominant in concentration than the other. [118,119] Progress A-E) Reproduced with permission: 2021, American Chemical Society [113] in life sciences has revealed that more diseases can affect the relative concentrations of these enantiomers, which can be exploited for disease detection. [120] Compared with other chiral sensing techniques, [121] bubble accumulation-assisted sensors have the unique advantages of (1) ultrahigh sensitivity (∼100 pM concentration), (2) low cost, and (3) high detection efficiency without sophisticated derivation and labeling, which are required with other methods, such as liquid chromatography coupled with mass spectrometry.…”
Section: Bpl For Clinical Detection Of Diabetesmentioning
confidence: 99%
See 1 more Smart Citation
“…19 A chiral electromagnetic field in the UV region, which matches the interband transition of noble metals, 20 could presumably perturb and even magnify the innate CD signals of biomolecules, 21,22 providing extra sensitivity, selectivity and reliability in chiral recognition. [23][24][25] Chiral biosensing in these two frequency regions should be different toward different chiral molecular structures, such as α-helices vs. β-sheets. Fabricating chiral metal nanostructures with strong optical activities in both the interband transition and plasmonic extinction regions would not only offer multiplexed detecting but also help us study the underlying mechanism of chiral biosensing.…”
Section: Introductionmentioning
confidence: 99%